EXPLORING THE USE OF TRANSLATOR APPLICATIONS: DO THEY IMPROVE ENGLISH LANGUAGE LEARNERS SKILLS - Akbar Nusantara, Bintang; Izzah, Navisatul (English Education Study Program STKIP PGRI Pacitan, 2024)
Translator application is a software program created to assist users in translating text, speech, or other forms of communication between different languages. Along with the increasing need to communicate with different languages, translator applications are becoming more used and constantly evolving. The appearance of translator application would make a certain effect on English language skills whether it is good or bad. This study aims to investigate the students’ perceptions of using translator applications to improve English skills. This researchused qualitative case study with semi-structured interview methods as its instruments. The participants were undergraduate students from non-English department who frequently use the translator applications. Based on the data obtained from the research, it shows that participants used several translator applications such as DeepL, Google Translate, Speak and Translate, Yandex Translate, Grammarly and Babylon Translator. The participants had different perspectives towards the effect of translator application on English skills. While the first participants believed thattranslator applications can improve his English skills since they provideassistance in grammar, the other participant concurred that translation applications inhibited learners’ ability to think and express themselves directly in English. This research article further explored the disadvantages of using the translator application completed with the strategy to maximize the advantages of these application.